Formulasi Diskresi Pada Penyelenggaraan Reformasi Birokrasi Di Kanwil Kementerian Agama Provinsi Jawa Tengah - Sarip Sahrul Samsudin; Y Setyohadi Pratomo (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
State administration is never separated from policy making. Bureaucratic reforms is carried out to realize good governance, therefore policy is a must because all the implementation of programs and community services should be conducted. One of the policies that is often carried out is discretion, with the aim of filling the regulatory vacuum and not stopping innovating in carrying out policies because of the regulatory vacuum. This study was conducted to analyze the formulation of discretion in the implementation of bureaucratic reform. This research was conducted with a qualitative approach. Results of the study: 1) discretion is carried out by taking into account the objectives, causes and conditions for using discretion; 2) discretion that is contrary to the objectives, procedures and conditions can be canceled; 3) it is necessary to build an accountability system in the implementation of discretion so that it does not lead to corrupt behavior. Conclusion: discretion is an innovation that can be accounted for by the government and society